Involvement of ESCRT-II in Hepatitis B Virus Morphogenesis - Stieler, Jens T. (Public Library of Science, 2014)
The hepatitis B virus (HBV) is an enveloped DNA virus that replicates via reverse transcription of its pregenomic RNA (pgRNA). Budding of HBV is supposed to occur at intracellular membranes and requires scission functions of the endosomal sorting complex required for transport (ESCRT) provided by ESCRT-III and VPS4. Here, we have investigated the impact of the upstream-acting ESCRT-I and ESCRT-II complexes in HBV morphogenesis. RNA interference knockdown of the ESCRT-I subunits TSG101 and VPS28 did not block, but rather stimulate virus release. In contrast, RNAi-mediated depletion of the ESCRT-II components EAP20, EAP30 and EAP45 greatly reduced virus egress. By analyzing different steps of the HBV maturation pathway, we find that the knockdown of ESCRT-II not only inhibited the production and/or release of enveloped virions, but also impaired intracellular nucleocapsid formation. Transcription/translation studies revealed that the depletion of ESCRT-II neither affected the synthesis and nuclear export of HBV-specific RNAs nor the expression of the viral core and envelope proteins. Moreover, the absence of ESCRT-II had no effects on the assembly capability and integrity of HBV core/capsids. However, the level of encapsidated pgRNA was significantly reduced in ESCRT-II-depleted cells, implicating that ESCRT-II directs steps accompanying the formation of replication-competent nucleocapsids, like e.g. assisting in RNA trafficking and encapsidation. In support of this, the capsid protein was found to interact and colocalize with ESCRT-II subunits in virus-producing cells. Together, these results indicate an essential role for ESCRT-II in the HBV life cycle and suggest that ESCRT-II functions prior to the final HBV budding reaction.